Studi Literatur Tentang Karakteristik Spesies Endemik Sulawesi Burung Maleo (Macrocepalon Maleo): Karakteristik Burung Maleo - Misnawaty Wantogia; Bempah, Irwan; Marini Susanti Hamidun (PT. Intelek Cendikiawan Nusantara, 2024)
Abstract The Maleo bird (Macrocephalon maleo) is an endemic species found only on Sulawesi Island, Indonesia. This species has unique characteristics and plays an important role in the biodiversity of the region. This bird is characterized by a black hard print on its head. The facial skin is yellow, with an orange beak and predominantly black feathers. Its body size is medium, with a length of about 55 centimeters. These animals have a unique way of reproduction, where they do not incubate their eggs but bury their eggs in sand warmed by natural geothermal heat until they hatch. Maleo eggs are very large, about 5 times the size of chicken eggs. as an endangered species according to the IUCN. The main threats to the survival of this species include habitat destruction, poaching of wildcatchers, and theft of their eggs. Various conservation efforts have been made to protect Maleo, including research, habitat protection, and public education. Conservation programs that involve the active participation of local communities and collaboration with conservation organizations. Maleo has an important ecological role in the Sulawesi ecosystem. Socially, Maleo is a symbol of biodiversity and local identity, and is the focus of conservation efforts involving the community